Assessment of left and right ventricular rotational interdependence: A speckle tracking echocardiographic study - Alizadehasl, Azin; Sadeghpour, Anita; Hali, Reza; Bakhshandeh Abkenar, Hooman; Badano, Luigi (Echocardiography (Mount Kisco, N.Y.), 2017)
Objective We sought to investigate the possible interdependence of the left (LV) and right ventricular (RV) rotational mechanics. Background Although myocardial fiber architecture and the effect of various pathologic conditions on LV torsional mechanics have already been investigated through multiple studies using different methods, there is still a significant debate about the actual presence and functional significance of RV rotational mechanics. Methods We perform a cross‐sectional prospective study of 118 subjects, including 19 normal subjects (NS, 35±7 years), 34 patients with severe aortic stenosis (AS, 44±16 years), 26 patients with nonobstructive hypertrophic cardiomyopathies (HCM, 46±18), and 39 patients with nonischemic dilated cardiomyopathies (DCM, 39±13 years). LV and RV rotational parameters were measured using velocity vector imaging. Total LV and RV apical segment rotations as well as the rotation of the free wall of RV apex were measured separately. Interdependence of the LV and RV rotational mechanics was assessed using the Spearman rho test. Results Both LV (7.3°±4.1° in NS, 11°±4.6° in AS, 7.7°±5.2° in HCM, and 1.9°±2° in DCM, P=<.0001) and RV apexes (4.7°±2° in NS, 6.1°±4° in AS, 3.2°±3.7° in HCM, and 2.4°±3.6° in DCM, P=<.0001) rotated counterclockwise in all the four study groups. Interventricular apical rotation interdependence was stronger in the AS (Spearman rho [ρ]: .716; P=.000) and in the HCM (ρ: .395; P=.04) subgroups than in the NS (ρ: .26; P=.27) and DCM (ρ: .215; P=.18). In DCM patients, RV apex rotation appeared to be independent of LV rotation. RV free wall apical rotation was larger than its corresponding value for the total apical segments in all studied groups. This difference was significant only in the AS (P=.007). Conclusion Our findings demonstrated a close correlation between RV and LV apical rotation parameters in different cardiac conditions as well as in normal subjects. However, in DCM patients, we also showed some independent rotation of the RV from the LV apex.